2016
DOI: 10.1128/aem.02381-16
|View full text |Cite
|
Sign up to set email alerts
|

Response of Germfree Mice to Colonization by Oxalobacter formigenes and Altered Schaedler Flora

Abstract: Colonization with Oxalobacter formigenes may reduce the risk of calcium oxalate kidney stone disease. To improve our limited understanding of host-O. formigenes and microbe-O. formigenes interactions, germfree mice and mice with altered Schaedler flora (ASF) were colonized with O. formigenes. Germfree mice were stably colonized with O. formigenes, which suggests that O. formigenes does not require other organisms to sustain its survival. Examination of intestinal material indicated no viable O. formigenes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…In an older study, male mice were found to be more susceptible to death after C. botulinum infection, which could be explained by their coprophagic behavior or a more general higher susceptibility to disease (36). In contrast, other studies reported an absence of gender-specific effects on, for instance, levels of Oxalobacter formigenes colonizing ASF mice (20) or the assembly of a synthetic microbiota (43). Whereas some studies discussed here (Tables 1 to 3) reported the use of a mixed-gender population, others included only one gender (n ϭ 12 of 53 studies), in which male animals were more often used than female animals (nine versus three).…”
Section: Host Parameters Influencing the Microbiotamentioning
confidence: 85%
See 1 more Smart Citation
“…In an older study, male mice were found to be more susceptible to death after C. botulinum infection, which could be explained by their coprophagic behavior or a more general higher susceptibility to disease (36). In contrast, other studies reported an absence of gender-specific effects on, for instance, levels of Oxalobacter formigenes colonizing ASF mice (20) or the assembly of a synthetic microbiota (43). Whereas some studies discussed here (Tables 1 to 3) reported the use of a mixed-gender population, others included only one gender (n ϭ 12 of 53 studies), in which male animals were more often used than female animals (nine versus three).…”
Section: Host Parameters Influencing the Microbiotamentioning
confidence: 85%
“…The applications of ASF in rodents varied from wild-type strains (mostly C57BL/6 but also C3H/HeN and Swiss Webster mice) to models prone to diseases, including irritable bowel disease (IBD) (15)(16)(17), type I diabetes (18), or colorectal cancer (19). The ASF lacks Proteobacteria, a phylum shared by mice and humans, whereas some researchers introduced Proteobacteria to ASF mice, such as Oxalobacter formigenes (20) and Escherichia coli (21). Other studies included only selected members of the ASF, because not all members were found to successfully colonize the murine cecum (18) or to test the levels of colonization resistance of different combinations of ASF members (22).…”
Section: (Altered) Schaedler Floramentioning
confidence: 99%
“…Experiments showed that these mono-colonized mice had significantly reduced urinary oxalate excretion compared to germ free mice. This finding may play an important role in the development of Oxf as probiotic [30]. …”
Section: Animal Studiesmentioning
confidence: 99%
“…Multiple gut microbes can degrade oxalate [22], including Oxalobacter formigenes, an oxalate autotroph [23][24][25][26][27]. When given to animals, O. formigenes has reduced host oxalate burden [28][29][30][31][32][33]. [44][45][46].…”
Section: Mainmentioning
confidence: 99%